Um estudo de curvas planas utilizando o GeoGebra - Miyasaki, Rodrigo (2017)
This paper proposes to make use of GeoGebra Software as a tool in the study of flat curves. The Software was chosen because it is a powerful tool in teaching learning at all levels of Mathematics because it works with Algebra and Geometry, allowing the user to perform algebraic and graphical operations in the same interface. The topics covered include the parameterized flat curves up to the study of the Frenet benchmark, making Geogebra an important tool for the study and visualization of the concepts covered. With the help of the Software we can better analyze the curves through their graphs.